Studies on Supplementation of Graded Levels of Millitia Ferruginea Leaf Meal on Feed Intake, Growth Performance and Carcass Charactfers of Arsi Bale Goats (Global Journal of Science Frontier Research, 2015)
The study was carried out to investigate the effect of supplementation of Millitia ferruginea leaf meal on intake, growth performance and carcass characteristics in intact Arsi Bale bucks fed a basal diet of grass hay. Twenty yearling male bucks with an initial body weight of 10.28 ± 0.96 kg (mean ± SE) were assigned to treatments using a completely randomized block design with four treatments i.e.T1 = 0% MLM + wheat bran+ maize and hay adlib,T2=2% MLM + wheat bran+ maize and hay adlib,T3=4% MLM wheat bran+ maize and hay adlib and T4=6% MLM + wheat bran maize and hay adlib One hundred gram concentrate mixture supplement was given twice a day in equal portions. The results indicated that there were no significant differences on feed intake, weight gain and feed conversion efficiency among the bucks receiving different treatments. The results pertaining to the carcass traits indicated differences ( in percentage terms) in un eviscerated carcass weight and dressing percentage with values higher among the bucks reared on T3 ration the weight of the empty gastrointestinal tract was also different between treatments with higher values observed in the bucks reared on T4 diet.
Keywords: millitia ferruginea leaf meal; bucks; feed intake; growth performance and carcass characteristics